2020
DOI: 10.1101/2020.10.14.338558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methyltransferase-like 3 modulates severe acute respiratory syndrome coronavirus-2 RNA N6-methyladenosine modification and replication

Abstract: The coronavirus disease 2019 pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is an ongoing global public crisis. Although viral RNA modification has been reported based on the transcriptome architecture, the types and functions of RNA modification are still unknown. In this study, we evaluated the roles of RNA N6-methyladenosine (m6A) modification in SARS-CoV-2. Our methylated RNA immunoprecipitation sequencing (MeRIP-Seq) analysis showed that SARS-CoV-2 RNA contained m6A modifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 62 publications
6
34
0
Order By: Relevance
“…Recently, the m6A methylation machinery was identified to play a key role in the context of SARS-CoV-2, with studies reporting widespread alterations of the viral and host RNA m6A methylome following infection [Xu et al (2021)]. Further, altered expression levels of methyltransferase-like 3 (METTL3) and fat mass and obesity-associated protein (FTO) linked to viral replication [Zhang et al (2020)]. FTO is a demethylase (eraser) enzyme with enriched binding in the 3’ UTR of mRNAs in mammals [Meyer et al (2012)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the m6A methylation machinery was identified to play a key role in the context of SARS-CoV-2, with studies reporting widespread alterations of the viral and host RNA m6A methylome following infection [Xu et al (2021)]. Further, altered expression levels of methyltransferase-like 3 (METTL3) and fat mass and obesity-associated protein (FTO) linked to viral replication [Zhang et al (2020)]. FTO is a demethylase (eraser) enzyme with enriched binding in the 3’ UTR of mRNAs in mammals [Meyer et al (2012)].…”
Section: Resultsmentioning
confidence: 99%
“…Altered expression levels of methyltransferase-like 3 (METTL3) and fat mass and obesity-associated protein (FTO) have been recently linked to viral replication (99). FTO is a demethylase (eraser) enzyme with enriched binding in the 3’ UTR of mRNAs in mammals (58).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed investigation is essential to understand whether SARS-CoV-2 RNA is subjected to m6A modifications and its role in virus replication and viral particle synthesis in the host cells. Moreover, a recent report has shown that SARS-CoV-2 protein interacts with host m6A machinery for efficient infection ( Zhang et al, 2020 ).…”
Section: Host Epigenetic Players In Generation Of Sars-cov-2 Virusmentioning
confidence: 99%
“…Especially, which can affect the replication of the virus and the host's innate immunity. A recent study has found that the host m6A modification complex interacted with SARS-CoV-2 proteins to modulate SARS-CoV-2 replication [13]. m 6 A epitranscriptome of Kaposi sarcomaassociated herpesvirus (KSHV) was recently mapped.…”
mentioning
confidence: 99%